Glass transition and degree of conversion of a light-cured orthodontic composite - Michela M. D. S. Sostena; Renata A. Nogueira; Carlos R. Grandini; João Carlos Silos Moraes (University of São Paulo, 2009)
OBJECTIVE: This study evaluated the glass transition temperature (Tg) and degree of conversion (DC) of a light-cured (Fill Magic) versus a chemically cured (Concise) orthodontic composite. MATERIAL AND METHODS: Anelastic relaxation spectroscopy was used for the first time to determine the Tg of a dental composite, while the DC was evaluated by infrared spectroscopy. The light-cured composite specimens were irradiated with a commercial LED light-curing unit using different exposure times (40, 90 and 120 s). RESULTS: Fill Magic presented lower Tg than Concise (35-84ºC versus 135ºC), but reached a higher DC. CONCLUSIONS: The results of this study suggest that Fill Magic has lower Tg than Concise due to its higher organic phase content, and that when this light-cured composite is used to bond orthodontic brackets, a minimum energy density of 7.8 J/cm² is necessary to reach adequate conversion level and obtain satisfactory adhesion.